AN ETHNOBOTANICAL SURVEY OF NADUVIL PANCHAYAT IN KANNUR DISTRICT KERALA - JERY THOMAS AND A.JOHN DE BRITTO (Ancient Science of Life, 1999)
The present paper reports the ethnobotanical uses of 32 plant species belonging to 31 genera of 25 families being practiced by tribals in Naduvil panchayat near “Paithalmala” hills in kannur district in kerala. The researchers collected information form the tribals about their medicinal practices. Vernacular name, botanical name, family, morphology of the useful parts and uses of medicinal plants and preparations of medicines are given. This study throws light on the plant human interaction.